Implementasi Metode Thresholding Dalam Mengenali Bentuk Citra Buah Salak - Preddy Marpaung; Miftahul Jannah; Bosker Sinaga (Jurnal Media Informatika, 2025)
Object shape recognition in digital images is a crucial aspect of image processing and computer vision. This study implements the thresholding method as a segmentation technique to identify the shape of salak fruit (snake fruit) in digital images. The thresholding technique is applied to separate the main object (salak fruit) from the background based on pixel intensity differences. The process involves image acquisition, grayscale conversion, and the application of thresholding to produce a binary image. Morphological analysis is then conducted to extract shape features from the segmented object. The results indicate that the thresholding method is effective in recognizing the shape of salak fruit, achieving good accuracy under well-contrasted lighting and background conditions. This implementation can serve as a foundation for automated fruit classification or identification systems based on digital image processing.